Impact of Pre-and Post-Equalization on the Performance of PNC - Ghanti, Basanti; R Patil, Rajendra (International Journal of Engineering and Technology, 2018)
The work presented considers a Physical Layer Network Coded (PNC) communication which is affected by Intersymbol Interference (ISI) due to Rayleigh fading channel. A pre-equalizer filter configured to combat the ISI is considered at the end nodes. The relay uses the Amplify and Forward (AF) strategy. The signal in the Multiple Access (MAC) phase is amplified at the relay and forwarded to the receiving nodes. The signal received by the end nodes in the broadcast (BC) phase is subjected to post-equalization by a receiver filter configured to overcome ISI. The performance of the PNC with only pre-equalizer applied, only post-equalization applied and the combined effect of pre-equalizer and post-equalizer is simulated .Simulation results indicate that the performance of PNC when only pre-equalizer applied , only post-equalization is applied are not much varying but better than the no equalization case. But the combined effect of pre-and post-equalization is much improved.Â Â
Keywords: PNC; Two-way relay channels; Amplify-Forward protocol; Sum-BER; Maximum sum-rate.